Pengaruh Penerapan Model Project Based Learning (PjBL) Terhadap Motivasi Belajar Warga Belajar Pendidikan Keaksaraan Berbasis Life Skill - Rudi Amir; Kartini Marzuki; Jumiati Jumiati; Fatmawati Gaffar (Universitas Negeri Makassar, 2022)
One of the learning models that can improve the ability to produce a product is project based learning. Through this learning model, students can produce a product. In addition, project-based learning is student-centered so that it can make them independent. This study examines the application of the project-based learning model and its impact on the learning motivation of independent business literacy students assisted by PKBM Hasanuddin Institute using a quantitative approach and experimental research types. Asa result of the research carried out, it is known that the project-based learning model and learning motivation, based on the percentage level in the category are quite good. As well as the results of the analysis through the t-test provide information that there is a significant impact between the project-based learning model on the learning motivation of independent business literacy students. This indicates that the model is very effectively applied to non-formal education program units whose concepts and practices are centered on independent projects or tasks that can make students active in following the learning process so that the ability to read, write and count is improved.